Regression of Cardiac Rhabdomyomas in a Neonate after Everolimus Treatment. (27th June 2016) - Bornaun, Helen; Öztarhan, Kazım; Erener-Ercan, Tugba; Dedeoğlu, Reyhan; Tugcu, Deniz; Aydoğmuş, Çiğdem; Cetinkaya, Merih; Kavuncuoglu, Sultan
Abstract : Cardiac rhabdomyoma often shows spontaneous regression and usually requires only close follow-up. However, patients with symptomatic inoperable rhabdomyomas may be candidates for everolimus treatment. Our patient had multiple inoperable cardiac rhabdomyomas causing serious left ventricle outflow-tract obstruction that showed a dramatic reduction in the size after everolimus therapy, a mammalian target of rapamycin (mTOR) inhibitor. After discontinuation of therapy, an increase in the diameter of masses occurred and everolimus was restarted. After 6 months of treatment, rhabdomyomas decreased in size and therapy was stopped. In conclusion, everolimus could be a possible novel therapy for neonates with clinically significant rhabdomyomas.